2019
DOI: 10.3389/fnmol.2019.00242
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Tau, p53 and Pin1 Regulate PARN-Mediated Deadenylation and Gene Expression

Abstract: While nuclear tau plays a role in DNA damage response (DDR) and chromosome relaxation, the mechanisms behind these functions are not fully understood. Here, we show that tau forms complex(es) with factors involved in nuclear mRNA processing such as tumor suppressor p53 and poly(A)-specific ribonuclease (PARN) deadenylase. Tau induces PARN activity in different cellular models during DDR, and this activation is further increased by p53 and inhibited by tau phosphorylation at residues implicated in neurological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 92 publications
(243 reference statements)
0
23
0
Order By: Relevance
“…Genetic alteration of P53 variants affects aging, cognitive decline, and TAU phosphorylation in mice [ 151 , 152 ]. Recently it has been found that P53 is part of a complex containing nuclear TAU, PIN1 and the polyA-specific ribonuclease PARN in the colon cancer cell line HCT116 [ 153 ], which are also rich in hyperphosphorylated TAU forms [ 154 ]. PARN-mediated nuclear deadenylation is activated by TAU, further potentiated by P53 and reduced by TAU phosphorylation.…”
Section: Possible Microtubules-independent Pathways Explaining Thementioning
confidence: 99%
“…Genetic alteration of P53 variants affects aging, cognitive decline, and TAU phosphorylation in mice [ 151 , 152 ]. Recently it has been found that P53 is part of a complex containing nuclear TAU, PIN1 and the polyA-specific ribonuclease PARN in the colon cancer cell line HCT116 [ 153 ], which are also rich in hyperphosphorylated TAU forms [ 154 ]. PARN-mediated nuclear deadenylation is activated by TAU, further potentiated by P53 and reduced by TAU phosphorylation.…”
Section: Possible Microtubules-independent Pathways Explaining Thementioning
confidence: 99%
“…More specifically, phosphorylation of nuclear tau negatively regulates its nuclear function in pluripotent neuronal cells and neuroblastoma cells 10 . Previous studies have revealed that nuclear tau plays a role in the DNA damage response (DDR) through deadenylation, which triggers major mRNA decay pathways 11,12 . Most recently, we found that oligomeric assemblies of tau containing RNA-binding proteins impair chromatin remodeling and nuclear lamina formation through associations with histones and chromatin components in the nuclear compartment 13 .…”
Section: Introductionmentioning
confidence: 99%
“…HuR occupies ARE to release NCL, p53, and PARN, and thereby stabilizes the p53 mRNA (X. Zhang et al, 2018). The activated p53 can bind with PARN and enhance its deadenylation activity towards nonessential transcripts (Devany et al, 2013), probably through a nuclear complex containing activated p53, tau, a tau‐binding protein Pin1, and PARN (Baquero et al, 2019). Therefore, PARN is involved in multiple feedback loops to control p53 mRNA and protein levels.…”
Section: Parn In Ddr and Genomic Stabilitymentioning
confidence: 99%